Avaliação dos parâmetros de eficiência na insensibilização por eletronarcose em indústria de processamento de carnes: aspectos relacionados ao planejamento e controle de manutenção - Fagundes Filho, João Carlos (2014)
The present study aimed to analyze the quality of stunning in a meat processing industry and the parameters related to Maintenance Planning and Control (PCM). It also defines what are the specific objectives and the overall goal of the work. The study covers the history, how it operates, importance and other relevant issues on the PCM, known types of stunning and animal welfare. Displays the description of the existing stunning equipment, stunning efficiency of control methods, besides the experiment to describe the current situation, suggest improvements and conclusions.